Enabling Transdisciplinary Collaboration: Stakeholder Views on Working With “Children With Mentally Ill Parents” Research Groups - Kaisler, Raphaela E.; Grill, Christiane (Frontiers in Psychiatry, 2021)
Working collaboratively and openly together with stakeholders has become a common phenomenon in research. While previous studies have gathered a clear picture on researchers’ attitudes, motivations, and barriers for actively involving stakeholders in transdisciplinary research, the stakeholder perspective is yet unknown. Therefore, this paper sets out to identify how stakeholders perceive transdisciplinary collaborations with researchers. This paper in particular reveals the enablers and barriers for such collaborations from the viewpoint of stakeholders. To do so, we look at how stakeholders, who were actively involved in the governance structure of two ‘children with mentally ill parents’ research groups in Austria, perceived their collaboration with researchers. We used a mixed-method, quantitative-qualitative design. We conducted an online survey and interviews with the members of the advisory board and competence group. These stakeholders reported great satisfaction with the transdisciplinary collaboration and emphasized the value of different expertise. As the most important enablers for successful, transdisciplinary collaboration stakeholders emphasized researchers’ open-mindedness towards new perspectives and approaches, flexibility to adapt to the research process along the way, and creativity dealing with diverse backgrounds and skills. Stakeholders further underlined the importance of a person facilitating the collaboration process between researchers and stakeholders to resolve any tensions and insecurities. Concluding, researchers’ attitudes, and in particular their understanding of the value of stakeholder involvement in research are key enablers for successful transdisciplinary research collaborations.